KARAKTERISASI EKSTRAK AIR KAYU SECANG (Caesalpinia sappan. L.) MENGGUNAKAN FOURIER TRANSFORM INFRARED (FTIR) - Rosalin; M. Yasser; Mahirullah; Elsa Nutrisari; Munnifah Anton, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Extraction of Sappan Wood (Caesalpinia sappan L.) has been carried out using water as a solvent with Ultrasound Assisted extraction. The water extract was subsequently characterized using Fourier Transform Infrared (FTIR) spectroscopy to determine the functional groups present in the extract. The characterization results using Infrared spectroscopy showed a wavenumber of 1500.67 cm-1 as an indicator of aromatic groups, and a wavenumber of 3456.55 cm-1 also indicated the presence of OH groups. Additionally, functional groups of alkenes (C=C) were obtained at a wavenumber of 1620.33 cm-1 and carboxylic acid groups (COOH) at a wavenumber of 1701.27 cm-1.